Consumers' skepticism towards advertising claims - Tien, Cheryl Marilyn (Curtin University, 2011)
The purpose of this study is threefold. It investigates (a) how personal and social influences affect consumers’ skepticism toward advertising claims (CSA) and how CSA influences inferences of manipulative intent (IMI), (b) the mediating role of attitude toward the advertisement between IMI and product judgment and (c) the moderating roles of brand familiarity and perceived risk on consumers’ skepticism toward advertising, inferences of manipulative intent and product judgment.